Sexual coercion and health-risk behaviors among urban Chinese high school students - Yi Song; Cheng-Ye Ji; Anette Agardh (Taylor & Francis Group, 2014)
Objective: To determine the association between health-risk behaviors and a history of sexual coercion among urban Chinese high school students. Design: A cross-sectional study was performed among 109,754 high school students who participated in the 2005 Chinese Youth Risk Behavior Survey. Data were analyzed for 5,215 students who had experienced sexual intercourse (1,483 girls, 3,732 boys). Multivariate logistic regression was used to determine the relationship between sexual coercion and the related covariates, and data were stratified by gender. Results: Of those students who had had sexual intercourse, 40.9% of the females and 29.6% of the males experienced sexual coercion (p<0.01). When analyses controlled for demographic characteristics, in the study sample, that is, students who had sexual intercourse, drug use (odds ratios [OR], 2.44), attempted suicide (OR, 2.30), physical abuse (OR, 1.74), binge drinking (OR, 1.62), verbal abuse (OR, 1.29), experience of being drunk (OR, 0.68), and smoking of cigarettes (OR, 0.52) were related to a history of sexual coercion. Patterns of health-risk behaviors also differed among female and male students who had experienced sexual coercion. Conclusions: Sexual coercion is associated with health-risk behaviors. Initiatives to reduce the harm associated with sexual coercion among high school students are needed.